Pegmatitos graníticos de Namirroé – Nuaparra, Zambézia, Moçambique – Estrutura e mineralogia - Gomes, C. Leal (2023)
At the core of the Granitic Pegmatite Province of Zambezia in Mozambique, in the Alto Ligonha Pegmatite District, a group of distinct types of pegmatites outcrop and are trapped by the same set of strike slip and overthrust structures. The most frequent are beryllium-rich with some Bi and Nb-Ta oxides (with anomalous contents of W). Their primordial inner structure is well preserved — giant crystals of K-feldspar are conspicuous, as is rose quartz in huge quantities at the core. At close proximity, LCT typical pegmatites do occur. On the basis of mineralogy, structure, and cartography, and considering the paragenetic contrasts and the emplacement in the same set of megascale structures of tectonic transport, it is reasonable to accept that this area corresponds to a material frontier between distinct districts or pegmatite fields.